Five get into a fix - Blyton, Enid. (b, 2004)
The Famous Five are skiing and having a brilliant time! But there's always a mystery to solve: such as who is living in the mysterious house near their chalet? The caretaker says the house if empty ... but the Five have seen a terrified face at the window ...
Keywords: Famous Five (Fictitious characters) -- Juvenile fiction; Abandoned houses -- Juvenile fiction; Missing persons -- Juvenile fiction